STRUCTURAL VANADIUM AND CHROMIUM IN LATERITIC IRON OXIDES: GENETIC IMPLICATIONS - Schwertmann U.; Pfab G. (My University, 1996)
In following up a recent proof of a structural substitution of octahedral FeIII by VIII and CrIII in synthetic goethite, the same substitution was now recorded in goethites and hematites from lateritic crusts. Substitution up to 0.018 mole mole?1 V/V + Fe is shown by congruent dissolution of Fe and V and by the presence of Fe2+ equivalent to structural V in an acid digest. On heating the samples up to 800oC, homogenous distribution of V disappeared; i.e., V is ejected from the structure of iron oxides and oxidized to form crystalline FeVO4 (shown by XRD). As a consequence, congruent dissolution no longer takes place as V dissolved rapidly and independently of Fe. Chromium also dissolved congruently with Fe but was not ejected from the structure on heating up to 800oC. Thermodynamic considerations, taking the standard redox potential of the FeII/FeIII couple adsorbed to iron oxide into account, reveal that iron oxides, formed in a partly anoxic environment, may incorporate VIII. Thus, as in clay minerals, VIII may be used as a redox-indicator for a former anoxic environment.